Gender Aspects of Modern Management: World Practices and Ukrainian Realities - Bezrukova, Nataliya; Krekoten, Iryna; Svichkar, Vitalii; Olijnyk, Yevgen (International Journal of Engineering and Technology, 2018)
The globalization processes taking place in modern economy shape new requirements for the development of managerial approaches aimed at ensuring the highest performance of companies. Gender diversity of top management can provide a comprehensive view of the top management of the company's development, improve its reputation and increase investor interest in the company. The purpose of this study is to analyze the gender aspects of the world and Ukraineâ€™s management practices. The paper analyzes a series of studies that prove the growing role of women in the top management of companies. The authors compare management styles of female and male managers.The specifics of gender issues in Ukraine are researched. The study has shown that employed women are more likely to be hired and, accordingly, they are more rarely employers and self-employed persons. Branches and activities that are mainly headed by women and those that are predominantly headed by men are highlighted. Â The authors came to the conclusion that under the conditions of the post-industrial economy there arise new factors of modern development, and the failure to consider them significantly reduces the efficiency of the functioning of companies and the state as a whole.Â Â